Rethinking South China Sea disputes : the untold dimensions and great expectations - Tseng, Hui-Yi Katherine (London ; New York : Routledge, 2017)
"The proposed book draws on the on-going South China Sea dispute, and the multifaceted challenges wrought by the South China Sea issue that requires an inter-disciplinary perspective. It employs legal-analytical methods, to emphasize the nuances of the role and interpretation of international law and treaties by China in different periods, while taking into account policy and strategic concerns, which generally cast great sways in decision-making. The re-introduction of interdisciplinary concerns straddling law and history illustrates that the historical dimension, which has long been neglected, is an emerging concern that poses looming dangers that may unexpectedly radicalize the friction. Contributing to debunking the mystique wrought by confrontations between a historical and a law-dominated perspective, these perspectives are supported by a more nuanced analytical framework, featuring theoretical concerns with a tinge of practicality. The South China Sea dispute aims to unveil a nuanced evolution of the issue with a confluence of inter-temporal law, policy and maritime practices in the South China Sea"--
The South China Sea under the colonial encounter in the 19th century -- Beyond territorial disputes: maritime issues and the revolutionary China -- A neglected dimension in South China Sea: fishing -- From the centre: the dash-line claim as a historical immaginarium or a quest for new course? -- From the centre: a proposal of jurisdiction right upon maritime spaces -- From the periphery: the South China Sea as a frontier and application of the maritime space jurisdiction right -- Echoing the Mandala legacy : rethinking ASEAN engagement in South China Sea -- From the periphery : state succession and the South China Sea disputes -- Conclusion.
A brief sketch of the award in thest arbitration on the South China Sea issue (Philippines v. China), issued on 12 July 2016, is included in Conclusion.--Page six.
Includes bibliographical references and index.
Keywords: Maritime boundaries -- Southeast Asia; South China Sea -- International status; Territorial waters -- Southeast Asia